Transformasi Supervisi dan Administrasi Pendidikan di Tengah Perubahan Kurikulum Nasional - Anggraini, Tiara; Yuniati, Suci; Kurniati, Annisah; Rahmi, Depriwana (CV. Lentera Literasi Indonesia, 2025)
Significant changes in educational supervision and administration procedures have been brought about by changes in Indonesia's national curriculum, particularly with the implementation of the Merdeka Curriculum. The purpose of this study is to examine how curriculum modifications impact the functions and tactics of educational administration and supervision at the level of educational units. A literature review using a descriptive qualitative technique is the research methodology employed. The study's findings suggest that in order to facilitate the adoption of the new curriculum, which places a strong focus on adaptability, teamwork, and technology use, educational supervision and administration must be transformed. Supervisors and administrative personnel must develop their capacity in order to meet the needs of a changing curriculum.